2022
DOI: 10.1186/s40795-022-00598-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of under-nutrition among under five children in Ethiopia based on 2019 Mini-Ethiopia Demographic and Health Survey: Generalized Linear Mixed Model (GLMM)

Abstract: Introduction Malnutrition is a major public health problem that is experienced by many developing countries, like Ethiopia. Though some studies were conducted to identify the magnitude and determinants of acute malnutrition among under-five children, there is a lack of evidence that is representative of all children in Ethiopia. Hence, this national-level data could be representative of all targets and provide us with updated information on the nation-wide magnitude of nutritional status among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Raru et al ( 2022 ) assert that the magnitude of stunting and wasting are relatively high in Ethiopia, which indicates that undernutrition is a public health concern among children. In addition, region, place of residence and age of the child were significantly associated with stunting, and region, household wealth index and age of the child were significantly associated with wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Raru et al ( 2022 ) assert that the magnitude of stunting and wasting are relatively high in Ethiopia, which indicates that undernutrition is a public health concern among children. In addition, region, place of residence and age of the child were significantly associated with stunting, and region, household wealth index and age of the child were significantly associated with wasting.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study conducted in Ghana, Nigeria, Uganda, and Kenya, only 29.9%, 8⋅36%, 7⋅3%, 23.9%, and 48.5% of children obtained the recommended minimum acceptable diet, respectively [ 17 – 20 ]. A study conducted in Ethiopia showed that only a small proportion of children received minimum dietary diversity and maternal knowledge of complementary feeding practices was low [ 21 24 ]. The magnitude of MAD varies from 7 to 74% in Ethiopia [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, Nigeria, Uganda, and Kenya, wherein 29.9%, 8⋅36%, 7⋅3%, 23.9%, and 48.5% of children, respectively, obtained the recommeded (13)(14)(15)(16). A study conducted in Ethiopia showed that only a small percentage of children received minimum dietary diversity and maternal knowledge of complementary feeding practices was low (17)(18)(19)(20). The magnitude of MAD varies from 7 to 74% in Ethiopia (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%